Clinical and oncological outcomes of surgery in Anorectal melanoma in Asian population: A 15 year analysis at a tertiary cancer institute. (2021) - Kottakota, Viswanth; Warikoo, Vikas; Yadav, Ajay Kumar; Salunke, Abhijeet; Jain, Abhishek; Sharma, Mohit; Bhatt, Supreet; Puj, Ketul; Pandya, Shashank
Highlights: Anorectal melanoma is associated with poor survival and prognosis; surgical treatment has remained controversial. Patients are likely to have higher incidence of nodal metastases, and local and distant recurrences. Preoperative clinicoradiological assessment should guide the selection of the treatment. Both APR (abdominoperineal resection) and WLE (wide local excision) have equal and uncompromising role in the management. Abstract: Introduction: Anorectal malignant melanoma (ARMM) is an aggressive malignancy with dismal prognosis and a 5-year survival rate less than 20% in most of the previous studies. The ideal surgical treatment has still remained controversial. This retrospective study aims at analysing the outcome in patients with ARMM treated with curative surgical resection. Patients and methods: This is a retrospective study of 38 patients of stage I anorectal malignant melanoma treated with curative surgical resection at our tertiary cancer institute. Results: WLE (Wide Local Excision) was carried out in 12 patients and APR (abdominoperineal resection) was done in 26 patients. The median overall survival of the entire group in this study was 20 months. Although the median overall survival of WLE patients was higher than those with APR (37 months versus 16 months, respectively), this was not a statistically significant event (P=0.317). The 1-, 2-, 3-, 5-year survival rates were similar with both APR and WLE with no significant difference in the 5-year survival rate (P=0.816); overall 5-year survival rate of just 13%. There were 3 long-term survivors in this study group who survived for more than 10 years. Conclusion: Most patients ultimately succumb to the disease regardless of the management. Both APR and WLE have significant roles in the management depending on the subset of patients selected. Local treatment should be preferred wherever possible. Abdominoperineal resection should be offered in nodal disease or in a recurrent setting.